Socio-Clinical Determinants of Pattern of Glycated Haemoglobin among Tuberculosis Patients attending DOTS Clinic in North-Central Nigeria - Sunday A. Owolabi; Kola M. Alabi; Louis O. Odeigah; Adedayo Y. Kofoworade; Anthonia N. Alabi; Olufunmilayo A. Taiwo; Eyitayo O. Adunmo; Kayode O. Olafimihan; Jameelu-deen O. Yusuff (Nigerian Frontline Medicine Journal)
BackgroundSeveral factors such as obesity and smoking, among others, have been associated with deranged glycated haemoglobin (HbA1c) in TB patients. Hyperglycaemia, measured by HbA1c, showed a significantly higher risk of unfavourable TB treatment outcomes. This study examined the influence of some factors on HbA1c among TB patients attending the DOTS clinic of the University of Ilorin Teaching Hospital.